Internalization of Siammasei in Learning Moral Beliefs in Class XI Madrasah Aliyah DDI Padanglampe Pangkep Branch - Rasna Rasna; Sampara Palili; Abdul Azis (Early Publishing, 2026)
This study aims to analyze the process, strategies, and impact of internalizing Siammasei values in Akidah Akhlak learning among Grade XI students at Madrasah Aliyah DDI Padanglampe, Pangkep Regency. A qualitative approach with a case study design was employed to gain an in-depth understanding of the phenomenon within the madrasa’s social and cultural context. The participants included teachers, students, the madrasa principal, and the vice principal for curriculum affairs. Data were collected through observation, interviews, and documentation, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation, member checking, and prolonged observation. The findings indicate that the internalization of Siammasei values, including sipakatau (mutual respect), sipakalebbi (mutual appreciation), and sipakainge (mutual reminding), is implemented through contextual learning, habituation, role modeling, and the reinforcement of school culture. The process occurs across cognitive, affective, and psychomotor domains, enabling students to understand and apply these values in their daily lives. The internalization of Siammasei values contributes to character development, strengthens positive social interactions, and fosters a religious and humanistic school culture. Its impact is reflected in students’ moral awareness, commendable behavior, and consistency in practicing ethical values within school, family, and community settings. This study concludes that the internalization of Siammasei values is an effective local wisdom-based strategy for character education and remains highly relevant to the needs of contemporary Islamic education.